THE CORRELATION BETWEEN EMPLOYMENT STATUS AND PARITY WITH PREECLAMPSIA - Fedelita Aistania Putri Putri; Prastiwi Novia Puspitasari Puspitasari; Nur Cholila Cholila (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Preeclampsia is a collection of symptoms that occur in pregnant women, during childbirth, and in the puerperium consisting of hypertension, and proteinuria. This study aims to analyze the relationship between employment status and parity with the incidence of pre-eclampsia in pregnant women. The population was all mothers who gave birth with pre-eclampsia/eclampsia at RSUD Dr. R Koesma Tuban in October – December 2020 a total of 43 mothers gave birth. The sampling using Total Sampling. The independent variables in this study were employment status with each nominal data scale and parity with ordinal data scale and the dependent variable in this study was preeclampsia with an ordinal data scale. Data analysis in this study used Spearman with the help of SPSS. Significant limitation if p-value < 0.05. The analysis using the Spearman obtained p-value = 0,057 because the p-value > 0.05 which indicates there is a weak correlation between employment status and pre eclamsia of pregnant women. The analysis using the Spearman statistical test obtained p-value = 0,811 because the p-value > 0.05 which indicates there is no correlation between parity and pre eclamsia of pregnant women.